VD_FINDINFO HC / 2020 / 647 vom 16. September 2020 - VD Tribunal cantonal (2020)
EXPULSION DE LOCATAIRE, MOTIVATION DE LA DEMANDE, REJET DE LA DEMANDE | 257d CO, 135 CPC (CH), 147 al. 1 CPC (CH), 257 CPC (CH), 311 al. 1 CPC (CH)